2019
DOI: 10.1007/s00382-019-04840-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of model resolution on Arctic sea ice and North Atlantic Ocean heat transport

Abstract: Arctic sea-ice area and volume have substantially decreased since the beginning of the satellite era. Concurrently, the poleward heat transport from the North Atlantic Ocean into the Arctic has increased, partly contributing to the loss of sea ice. Increasing the horizontal resolution of general circulation models (GCMs) improves their ability to represent the complex interplay of processes at high latitudes. Here, we investigate the impact of model resolution on Arctic sea ice and Atlantic Ocean heat transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 66 publications
22
80
0
Order By: Relevance
“…In the ensemble of models examined, those with a higher resolution have a more saline and dense west SPG, a stronger AMOC and a greater AMOC weakening. Other studies have shown higher resolution models having a stronger AMOC (Roberts et al 2016(Roberts et al , 2019aSein et al 2018;Menary et al 2018;Docquier et al 2019;Hirschi et al 2020), however most of these studies (and all of the models in this study) have used the same ocean submodel (NEMO). Some other modelling studies have come to the opposite conclusion (Yokohata et al 2007;Delworth et al 2012;Winton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ensemble of models examined, those with a higher resolution have a more saline and dense west SPG, a stronger AMOC and a greater AMOC weakening. Other studies have shown higher resolution models having a stronger AMOC (Roberts et al 2016(Roberts et al , 2019aSein et al 2018;Menary et al 2018;Docquier et al 2019;Hirschi et al 2020), however most of these studies (and all of the models in this study) have used the same ocean submodel (NEMO). Some other modelling studies have come to the opposite conclusion (Yokohata et al 2007;Delworth et al 2012;Winton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The models configured for HighResMIP and used here are as follows: ECMWF-IFS (Roberts et al 2018); CNRM-CM6-1 (Voldoire et al 2019); CMCC-CM2-(V)HR4 (Cherchi et al 2019); HadGEM3-GC3.1 (Roberts et al 2019a); EC-Earth3P (Haarsma et al 2020). The model parameter settings are discussed in Docquier et al (2019) and Roberts et al (2019b). Note that all these coupled models use the NEMO ocean model, though with a range of configurations.…”
Section: Primavera Ensemblementioning
confidence: 99%
See 1 more Smart Citation
“…OHT provided a very poor predictive skill. Docquier et al (2019) recently showed (their Fig. 12) a relatively good correlation between OHT and the SIV.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, the 2 configurations from the same model keep the parameters identical, except for the resolution-dependent parameterizations (Docquier et al, 2019). In terms of ocean-sea ice grid, both AWI versions (data source: Semmler et al (2017b, a)) use a mesh grid with varying resolution.…”
mentioning
confidence: 99%